2016
DOI: 10.1016/j.devcel.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Variable Cell Growth Yields Reproducible Organ Development through Spatiotemporal Averaging

Abstract: Organ sizes and shapes are strikingly reproducible, despite the variable growth and division of individual cells within them. To reveal which mechanisms enable this precision, we designed a screen for disrupted sepal size and shape uniformity in Arabidopsis and identified mutations in the mitochondrial i-AAA protease FtsH4. Counterintuitively, through live imaging we observed that variability of neighboring cell growth was reduced in ftsh4 sepals. We found that regular organ shape results from spatiotemporal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
251
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(269 citation statements)
references
References 130 publications
(164 reference statements)
6
251
2
Order By: Relevance
“…It has also been shown in Arabidopsis thaliana that stress‐responsive genes are shorter (Aceituno et al , ), in agreement with the fact that HVGs are enriched in environmentally responsive genes. Our results are further supported by previous studies showing that genetic factors can control or buffer inter‐individual phenotypic variability in Arabidopsis thaliana (Hall et al , ; Jimenez‐Gomez et al , ; Folta et al , ; Hong et al , ; Schaefer et al , ). Cis factors have also been shown to regulate gene expression variability in other organisms: TATA boxes are linked to gene expression variability in yeast (Blake et al , ), and the strength of cis‐regulatory elements affects transcriptional noise in mammals (Suter et al , ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has also been shown in Arabidopsis thaliana that stress‐responsive genes are shorter (Aceituno et al , ), in agreement with the fact that HVGs are enriched in environmentally responsive genes. Our results are further supported by previous studies showing that genetic factors can control or buffer inter‐individual phenotypic variability in Arabidopsis thaliana (Hall et al , ; Jimenez‐Gomez et al , ; Folta et al , ; Hong et al , ; Schaefer et al , ). Cis factors have also been shown to regulate gene expression variability in other organisms: TATA boxes are linked to gene expression variability in yeast (Blake et al , ), and the strength of cis‐regulatory elements affects transcriptional noise in mammals (Suter et al , ).…”
Section: Discussionsupporting
confidence: 89%
“…It is not known whether such inter‐individual phenotypic variability originates from responses to microenvironmental perturbations, or from stochastic factors at the cellular level or from both. Differences in the level of inter‐individual variability have been observed between natural accessions, in recombinant inbred lines and also in mutants for many traits such as growth, hypocotyl length, leaf and flower number, plant height and plant defence metabolism (Hall et al , ; Jimenez‐Gomez et al , ; Folta et al , ; Hong et al , ; Schaefer et al , ). Jimenez‐Gomez and colleagues also identified QTLs explaining differences in the level of expression variability between pools of plants in Arabidopsis thaliana (Jimenez‐Gomez et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For each replicate, we performed RNA-seq on 250 dissected whole stage 12 sepals. At stage 12, cells in the sepal have fully differentiated and cell division and endoreduplication has been completed (Roeder et al, 2012; Hervieux et al, 2016; Hong et al, 2016). This strategy allowed us to assess sepal transcriptomes in their final, differentiated state: expressing terminal genes that might be driven by LGO in mature sepals, rather than others (e.g., cell-cycle genes, or developmental regulatory genes) that might be driven by LGO in earlier stages of sepal development.…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al compared ROS levels between wild‐type and mutant sepals and demonstrated that FtsH4 mutants have higher levels of both hydrogen peroxide (H 2 O 2 ) and superoxide (O 2 − ). Further, the O 2 − gradient patterning paralleled the pattern of cellular maturation from the tip to the base of wild‐type sepals . Decreasing ROS levels promotes sepal growth as overexpression of ROS‐quenching enzymes resulted in larger sepal sizes.…”
Section: Feedback From Physiological Signaling Ensures Robustness Of mentioning
confidence: 80%
“…To investigate how plants maintain robustness of morphogenesis, Hong et al screened for thale cress Arabidopsis mutants with disrupted sepal uniformity (reduced robustness) within an individual plant, and isolated several variable organ size and shape ( vos ) mutants. Interestingly, vos1 mutants have increased variability in sepal size and shape due to reduced local spatial variability in the cell growth of vos1 sepals . Genetic analysis and map‐based cloning determined that the vos1 phenotype is caused by recessive mutations in the mitochondrial protease gene FtsH4 .…”
Section: Feedback From Physiological Signaling Ensures Robustness Of mentioning
confidence: 99%